The Issue Of Islamic Education: A Perspective By Ramli Abdul Wahid - Mangunsong, Irvan; Arsyad, Junaidi; Ok, Azizah Hanum (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to explore the issues and solutions regarding Islamic education from the perspective of Ramli Abdul Wahid. Employing a qualitative method with a figure study approach, the study reveals six problems in Islamic education according to Ramli, including the emergence of SKB 3 Ministers, insufficiently compotent educators, lack of enthusiasm among students for academic studies, proliferation of fake academic degrees, a lack of proficiency in Arabic language, and a lack of moral education. The primary solution to these issues as identified by Ramli Abdul Wahid, lies in fostering awareness among students, educators, and parents that Indonesia lags behind in the field of education compared to other countries, including neighboring ones. Consequently, there should be a growing determination to address this educational lag.